2007
DOI: 10.4269/ajtmh.2007.77.883
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Characterization of Spotted Fever Group Rickettsiae in Taiwan

Abstract: Rickettsioses are emerging infectious diseases caused by rickettsiae in association with arthropods. We report the detection of spotted fever group rickettsiae (SFGR) in Taiwan using molecular methods. Phylogenetic analyses of the 17-kd protein and citrate synthase (gltA) genes showed that SFGR TwKM01 detected in Rhipicephalus haemaphysaloides ticks was most similar to Rickettsia rhipicephali. Three TwKM01 isolates were obtained from three individual R. haemaphysaloides ticks. Small, intracellular, coccobacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 49 publications
2
66
0
3
Order By: Relevance
“…1,2 Since then, the bacterium has been reported infecting a number of invertebrate species, including fleas, mosquitoes, ticks, mites, and booklice. [3][4][5][6][7][8] Despite an apparent broad host range, the majority of the literature reports of R. felis have been on fleas of the genus Ctenocephalides; namely, C. felis felis and Ctenocephalides canis collected from domestic dogs and cats. [9][10][11][12] In Brazil, R. felis was reported infecting Ctenocephalides fleas in the states of Sã o Paulo, Minas Gerais, and Rio de Janeiro, all in the Southeastern region of the country.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Since then, the bacterium has been reported infecting a number of invertebrate species, including fleas, mosquitoes, ticks, mites, and booklice. [3][4][5][6][7][8] Despite an apparent broad host range, the majority of the literature reports of R. felis have been on fleas of the genus Ctenocephalides; namely, C. felis felis and Ctenocephalides canis collected from domestic dogs and cats. [9][10][11][12] In Brazil, R. felis was reported infecting Ctenocephalides fleas in the states of Sã o Paulo, Minas Gerais, and Rio de Janeiro, all in the Southeastern region of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies revealed their role in the transmission of Rickettsia (Hsu et al, 2011). Tsui et al, (2007) detected spotted fever group rickettsial organism in R. haemaphysaloides using molecular methods in Taiwan. Experimental transtadial transmission of Babesia microti through R. haemaphysaloides in southern China was also reported (Li et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Although there are no known human cases of infections caused by spotted fever group (SFG) rickettsiae in Taiwan, novel strains of SFG rickettsiae have been isolated as recently described (6,7). In addition, evidence for R. felis infections in cat and cat fl ea populations has been identifi ed by using immunofl uorescence assay (IFA), PCR, and organism isolation (K.-H.Tsai et al, unpub.…”
Section: Human Case Of Rickettsia Felis Infection Taiwanmentioning
confidence: 99%
“…We collected fl eas by using a kerosene lamp hung above a 45-cm diameter tray containing water (7). Captured fl eas were identifi ed using a dissecting microscope and standard morphologic keys, sorted into vials by species and locality, and preserved in 70% ethanol (7).…”
Section: Kun-hsienmentioning
confidence: 99%
See 1 more Smart Citation